Meningkatkan Keterlibatan Perempuan Dalam Pengembangan UMKM Berbasis Pengetahuan Khas Perempuan Kota Kendari - Yuni Maimuna; Diamond Limbong; Sriayu Pracita (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to increase Micro, Small, and Medium Enterprises (MSME) involving women with particular knowledge. The population of this study was MSMEs in Kendari city, especially fashions, crafts, and culinary industries. The samples were collected by using the purposive sampling technique. The software used to analyze the data is WarpPLS 5.0. The outcome of this study showed that these female entrepreneurs emphasized the owner’s equity for initial capital. Both married and unmarried female entrepreneurs obtain family support to run their businesses. In addition, the self-independence that these women have is outstanding, particularly toward MSME development, in order that a woman should not rely on someone else to help their family financially and can generate jobs. Furthermore, women’s involvement in MSME development is excellent because women deserve to fully manage finance, do business, and have a side job at the same time.